Investigation of the mechanism of binding of thiacloprid to human serum albumin using spectroscopic techniques and molecular modeling methods. Issue 2 (2011) - Wang Wang, Chuanxian Chuanxian; Chu Chu, Qinghua Qinghua; Chen Chen, Changyun Changyun; Bo Bo, Zhao Zhao
Abstract : Fluorescence spectroscopy, UV absorption, circular dichroism (CD) spectroscopy and molecular modeling methods were used to characterize the binding properties of thiacloprid (TL) with human serum albumin (HSA) at molecular level under physiological conditions. The fluorescence intensity of HSA decreased regularly with the gradually increasing concentration of thiacloprid. The binding constant K at three different temperatures (290, 300 and 310 K) were 3.07, 2.74 and 1.35 × 10 4 M −1, respectively, for TL–HSA interaction have been calculated from the relevant fluorescence data. CD spectroscopic measurements have shown that the secondary structures of the protein have been changed by the interaction of thiacloprid with HSA. Furthermore, the study of molecular modeling indicated that thiacloprid could be located on the surface of the binding pocket of subdomains IIA in HSA. The hydrophobic interaction was the major acting force and there are H-bonds and electrostatic interactions between TL and HSA, which is in good agreement with the results from the experimental thermodynamic parameters (the enthalpy change ΔH 0 and the entropy change ΔS 0 were calculated to be −20.378 kJ/mol and 16.328 J/mol K according to the Van9t Hoff equation).